Revealing male bodies - Tuana, Nancy (Indiana University Press, 2002)
Revealing Male Bodies is the first scholarly collection to directly confront male lived experience. There has been an explosion of work in men's studies, masculinity issues, and male sexuality, in addition to a growing literature exploring female embodiment. Missing from the current literature, however, is a sustained analysis of the phenomenology of male-gendered bodies. Revealing Male Bodies addresses this omission by examining how male bodies are physically and experientially constituted by the economi.